Global Fatigue Life Modelling of Steel Half-pipes Bolted Connections. (2016) - Jovašević, S.; Correia, J.A.F.O.; Pavlović, M.; Rebelo, C.; De Jesus, A.M.P.; Veljković, M.; da Silva, L. Simões
Abstract: A steel hybrid structural solution for onshore wind turbine towers was proposed in the European project SHOWTIME. This solution is used in the lattice structure for the lower portion of the tower. Recently, a procedure for fatigue life estimation of steel half-pipes bolted connections applied in global structural models using multiaxial Smith-Watson-Topper (SWT) criteria was proposed by Öztürk et al. In this paper a procedure for design S-N curve modelling of steel half-pipes bolted connections is proposed. This procedure is based on a local approach using multiaxial fatigue criteria together with an elastoplastic analysis using the finite element method. The materials to be used in this analysis are the S355 and S690 steels. This evaluation to be performed is calibrated with experimental results of fatigue tests of the connection under consideration.